Milrinone in Enterovirus 71 Brain Stem Encephalitis - Wang, Shih-Min (Frontiers in Pharmacology, 2016)
Enterovirus 71 (EV71) was implicated in a widespread outbreak of hand-foot-and-mouth disease (HFMD) across the Asia Pacific area since 1997 and has also been reported sporadically in patients with brain stem encephalitis. Neurogenic shock with pulmonary edema (PE) is a fatal complication of EV71 infection. Among inotropic agents, milrinone is selected as a therapeutic agent for EV71- induced PE due to its immunopathogenesis. Milrinone is a type III phosphodiesterase inhibitor that has both inotropic and vasodilator effects. Its clinical efficacy has been shown by modulating inflammation, reducing sympathetic over-activity, and improving survival in patients with EV71-associated PE. Milrinone exhibits immunoregulatory and anti-inflammatory effects in the management of systemic inflammatory responses in severe EV71 infection.